Finance and economic growth: financing structure and non-linear impact - Peter Benczur; Stylianos Karagiannis; Virmantas Kvedaras (Publications Office of the European Union, 2017)
There is growing evidence that the impact of financial development on economic growth might be non-linear and hump-shaped, exhibiting a turning point. However, such findings are typically established using total finances (mostly: credit), and the apparent non-linear impact of totals can stem from a substantial structural change in the composition of finances, that has been taking place during the recent decades. Though there are some studies going beyond total finances, they usually look at the impact of certain financing components separately or using ratios, which may bias the estimation and lead to incorrect conclusions. Finally, the findings are typically based on a global pool of countries, and may be driven by a developing versus developed country differential. Focusing on groups of high-income countries (from the OECD, EU, and EMU), this study shows that the finding of a non-linear, hump-shaped impact of financing on economic growth is robust to controlling for financing composition in terms of the sources (bank credit, debt securities, stock market) and the recipients of finances (households, non-financial and financial corporations), or both. In particular, we obtain the following results. (1) The non-linear impact of total bank credit is more pronounced than that of either household credit alone, or the sum of bank credit, debt securities, and stock market financing. (2) Credit to non-financial corporations tends to have a positive, while credit to households a negative impact on growth, even after allowing for non-linearities. (3) Debt-securities and stock market-based financing have a different impact on growth. (4) The estimated turning point of the non-linear relationship is close to that found by Cournède and Denk (2015) for the OECD countries, and lower than that established by Arcand et al. (2015) for a broad set of countries.
Keywords: E44; G2; O4; 330; financial development; economic growth; finance-growth nexus; non-linearity; bank credit; debt securities; stock markets